Identification of two bitter components in Zanthoxylum bungeanum Maxim. and exploration of their bitter taste mechanism through receptor hTAS2R14. (15th February 2021) - Ke, Jingxuan; Cheng, Jinxi; Luo, Qingying; Wu, Hejun; Shen, Guanghui; Zhang, Zhiqing
Highlights: Identified key bitter compounds in Z. bungeanum using sensory and LC-MS techniques. 7-methoxycoumarin and 8-prenylkaempferol are key bitter compounds in Z. bungeanum . Contents of 7-methoxycoumarin and 8-prenylkaempferol in tested samples were varies. 7-methoxycoumarin and 8-prenylkaempferol can activate bitter taste receptor hTAS2R14. Abstract: Bitterness is an inherent organoleptic characteristic affecting the flavor of Zanthoxylum bungeanum Maxim. In this study, the vital bitter components of Z. bungeanum were concentrated through solvent extraction, sensory analysis, silica gel chromatography, and thin-layer chromatographic techniques and subsequently identified by UPLC-Q-TOF-MS. Two components with the highest bitterness intensities (BIs), such as 7-methoxycoumarin and 8-prenylkaempferol were selected. The bitter taste perceived thresholds of 7-methoxycoumarin and 8-prenylkaempferol were 0.062 mmol/L and 0.022 mmol/L, respectively. Moreover, the correlation between the contents of the two bitter components and the BIs of Z. bungeanum were proved. The results of siRNA and flow cytometry showed that 7-methoxycoumarin and 8-prenylkaempferol could activate the bitter receptor hTAS2R14. The results concluded that 7-methoxycoumarin and 8-prenylkaempferol contribute to the bitter taste of Z. bungeanum .